2016
DOI: 10.1039/c5ra05829e
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquids: the view from Mount Improbable

Abstract: The ionic liquid literature has grown at a remarkable rate since 1998, making it increasingly difficult to assess the important research directions and the underlying, fundamental understanding of ionic liquids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 32 publications
0
45
0
2
Order By: Relevance
“…These fluids show quite high thermal, oxidative, and radiological stability relative to many molecular organic solvents. 26 This has resulted in a wide range of reviews and books which summarise the properties, scope, and applications of these Coulombic fluids. 22 Ionic liquids show little tendency for causing corrosion of typical industrial materials, and may even inhibit corrosion.…”
Section: Rationalementioning
confidence: 99%
“…These fluids show quite high thermal, oxidative, and radiological stability relative to many molecular organic solvents. 26 This has resulted in a wide range of reviews and books which summarise the properties, scope, and applications of these Coulombic fluids. 22 Ionic liquids show little tendency for causing corrosion of typical industrial materials, and may even inhibit corrosion.…”
Section: Rationalementioning
confidence: 99%
“…In addition, these novel compounds were erroneously considered as non‐volatile and green solvents, although toxicity and volatility issues have been demonstrated for some ILs . Despite all these problems, the growth of the number of patents and industrial applications demonstrates that the ionic liquid field remains innovative and stimulating. Furthermore, the appearance of ILs mixtures increases the number of possibilities of functionalized compounds and their corresponding new applications …”
Section: Introductionmentioning
confidence: 99%
“…Over recent decades, the field of ionic liquids (ILs) has become one of the most popular areaso fr esearch owing to their adhoc designablep roperties for aw ide range of applications, [1][2][3] and consequently,t he number of publications in the field has grown exponentially.H owever,t his rapid growth has not been accompanied by the required characterization of the used ILs, and there is alackofd eep studies about ILs recovery and recycling, essential for economic viability in industrial applications. [1] In addition, these novel compounds were erroneously considered as non-volatile and green solvents, although toxicity and volatility issues have been demonstrated fors ome ILs. [4,5] Despitea ll these problems, the growth of the number of patentsa nd industrial applications [1] demonstrates that the ionic liquid field remains innovativea nd stimulating.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, it was found that ILs with coordinating anions, such as [OAc] − , were able to dissolve drugs at room temperature, which was attributed to the formation of hydrogen bonds. Biomedical applications of ILs are expected to become one of the major research trends in the next decade . New applications have appeared due to the existence of halogen‐bonding interactions in ILs.…”
Section: Introductionmentioning
confidence: 99%